Estágio curricular supervisionado no curso de pedagogia em tempos de pandemia – COVID-19: vivências e desafios - Almeida, Yasmim Martins De (Universidade Federal do Tocantins, 2023)
This qualitative approach research, with descriptive and bibliographic research, aimed to investigate the challenges experienced by the academics of the Pedagogy Course, from the Federal University of Norte do Tocantins, Tocantinópolis-TO Campus, during the Curricular Activity of Supervised Internship carried out through the Emergency Remote Teaching (ERE), due to the COVID-19. Students and teachers of the pedagogy course of the three classes of Supervised Internship that were offered in the 1st Semester of 2021, one class of Early Childhood Education and two of Elementary School participated in this research. A total of 20 students and 03 teachers participated in the research. The techniques used for data collection were two structured and semi-structured questionnaires prepared on the virtual platform Google Forms, one specific for students and another for teachers of internship disciplines. The results indicate that the main challenges experienced during the internship disciplines were the lack of face-to-face contact as well as the lack of access to a quality internet connection and the lack of knowledge and skill on the part of students with digital media. . However, despite the challenges and difficulties posed by the COVID-19 pandemic, the students participating in this research were able to positively carry out the subjects successfully, so that it was possible to obtain new learning for their training as well as a greater learning about digital media. This qualitative approach research, with descriptive and bibliographic research, aimed to investigate the challenges experienced by the academics of the Pedagogy Course, from the Federal University of Norte do Tocantins, Tocantinópolis-TO Campus, during the Curricular Activity of Supervised Internship carried out through the Emergency Remote Teaching (ERE), due to the COVID-19. Students and teachers of the pedagogy course of the three classes of Supervised Internship that were offered in the 1st Semester of 2021, one class of Early Childhood Education and two of Elementary School participated in this research. A total of 20 students and 03 teachers participated in the research. The techniques used for data collection were two structured and semi-structured questionnaires prepared on the virtual platform Google Forms, one specific for students and another for teachers of internship disciplines. The results indicate that the main challenges experienced during the internship disciplines were the lack of face-to-face contact as well as the lack of access to a quality internet connection and the lack of knowledge and skill on the part of students with digital media. . However, despite the challenges and difficulties posed by the COVID-19 pandemic, the students participating in this research were able to positively carry out the subjects successfully, so that it was possible to obtain new learning for their training as well as a greater learning about digital media. Keywords: Pedagogy Course. Supervised Curricular Internship. Emergency Remote Teaching. Pandemic.